Increased Student Motivation and Learning Outcomes Using the Grade 4 Problem Based Learning Model - Alvionita, Anita; Nurkholis, Nurkholis; Rinto, Rinto (Jurnal Edusci, 2023)
Based on the formulation of the problem above, the goal to be achieved in this study is to find out the increase in learning outcomes through students' learning motivation using the PBL (Problem Based Learning) learning model in learning Science Chapter 8 Class 4 at SD Negeri 2 Babakanmulya. The approach used in this research is qualitative. The increase in science learning outcomes was known by the test results in Cycle I and Cycle II which showed an increase in the average score and percentage of classical completeness. In this study, referring to indicators of success, the value calculated is the percentage of classical completeness if student learning outcomes are ≥ 85% of the total number of students in one class getting a score of ≥ 75. The average score of students in chapter 8 "Building a Civilized Society" Topic A and Topic B in the initial conditions (pre-cycle) 72 with classical completeness of 77% (20 students) of 26 students who achieved a score of ≥ 75 (KKM score).